FAMILY FUNCTION AND SELF-HARM BEHAVIOR IN EARLY ADOLESCENTS: A CROSS-SECTIONAL STUDY - Endah Luthfiana Sari; Yeni Fitria; Enggal Hadi Kurniyawan; Erti Ikhtiarini Dewi; Fitrio Deviantony (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2024)
Introduction: Self-harm behavior represents a maladaptive coping mechanism that can be highly harmful, potentially leading to injury or even posing a threat to an individual's life. Various factors contribute to self-harm behavior in early adolescence, with family dysfunction being one significant element. This study aimed to explore the relationship between family functioning and self-harm behavior among early adolescents in the Agricultural Area of Jember. Method: This study used a correlational design with a cross-sectional approach. The research sample was obtained through a proportional stratified random technique with 376 respondents. The independent variable in this study is family function, and the dependent variable is self-harm behavior in early adolescents. Data was collected using the Family APGAR and Deliberate Self-harm Inventory (DSHI) questionnaires. Results: The result showed that family function is in the high category, 224 respondents (59,6%), and self-harm behavior is low self-harm, 319 respondents (84,8%). There is a relationship between family function and self-harm behavior in early adolescents in the agricultural area of Jember (p = 0,001 and r =-0,131) very weak and negative correlation. Poor communication among family members can lead to inner conflict and negative emotions, increasing the risk of self-harm. The data was analyzed using Kendall's Tau C correlation test. Conclusions: Early adolescents from families with low functioning are at a higher risk of engaging in self-harm. This study can serve as a guideline for schools, psychiatric nurses, and community nurses to develop effective nursing interventions for early adolescents who exhibit self-harm behavior.